TRADISI ADAT KALOMBA: KAJIAN MAKNA DAN NILAI BUDAYA PADA MASYARAKAT DESA BONTO BIRAENG KABUPATEN BULUKUMBA - Ainun syafitri Muslimin; Andi Kurniawan; Nunu Vebriani; Nurul Hikmah (Titian: Jurnal Ilmu Humaniora, 2021)
AbstractThe purpose of this study is to determine the process of the Kalomba tradition, meanings and valuescontained in the traditional process of the Kalomba tradition. Kalomba tradition is a tradition carriedout by the Kajang Tribe aimed at the age of children to avoid skin diseases. The method used in thisresearch is qualitative with an ethnographic approach. Determination of informants using purposivesampling and snowball sampling. Data collection was carried out through interviews, observation anddocumentation as well as data analysis consisting of data collection, data reduction, data presentationand deduction. The results of this study revealed that the Kalomba tradition began during the KaraengPadulu Soreang period whose marriage was not approved and then a child was born. When parentswho do not agree to meet must fulfill these terms and conditions, this is known as Kalomba. Thetraditional Kalomba tradition is carried out based on stages starting from the ma'jenne procession,burning incense and lighting candles, reading prayers, waving incense smoke, tompong procession,baccing children procession, paddingi-dingi stage, massolo (giving money to children) and the eventends the setting of kampalo on eating together by family and relatives.The meaning of the Kalombatradition is as medicine and safety to avoid skin diseases and as a thanks giving from parents tochildren. The Kalomba tradition reveals the value of helping each other and togetherness, establishingfriendship and responsibility.